2018
DOI: 10.4028/www.scientific.net/jera.34.116
|View full text |Cite
|
Sign up to set email alerts
|

Lead Time Reduction through Execution of Lean Tool for Productivity Enhancement in Small Scale Industries

Abstract: In the current dynamic global market place, especially among small and medium scale manufacturing industries the competition is show rigorous for a profitable survival. To be competent the industries have to necessarily work in an efficient way by updating and implementing new techniques. These day’s manufacturers may have to introduce and prove the success of the products not only faster but also to deliver it to the end users at the right time. The aim of this study has been to present a lean approach in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 22 publications
(24 reference statements)
0
16
0
4
Order By: Relevance
“…For example, Cakmakci (2009) found that setup time reduction positively impacts the operational performance and is suitable practice not only for manufacturing improvement but also for equipment design development. Saravanan et al (2018) results indicate the setuptime reduction improves productivity by reducing the equipment downtime.…”
Section: Lean Practices Impact On Production Swiftness and Evennessmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, Cakmakci (2009) found that setup time reduction positively impacts the operational performance and is suitable practice not only for manufacturing improvement but also for equipment design development. Saravanan et al (2018) results indicate the setuptime reduction improves productivity by reducing the equipment downtime.…”
Section: Lean Practices Impact On Production Swiftness and Evennessmentioning
confidence: 91%
“…Amongst these factors, six of them were related to standardisation, streamlining, operational time, process design, waste and efficiency. These factors are the focus of common practices associated with lean manufacturing, such as setup time reduction (Saravanan et al, 2018;Curado, 2019), process redesign (Al-Salim and Choobineh, 2009;Keil et al, 2011;Bergenwall et al, 2012), cellular manufacturing (Angra et al, 2008;Safaei et al, 2010), throughput time reduction (Muthiah et al, 2008, Van Der Heijden et al, 2012 and factory automation (Muthiah et al, 2008;Figueiredo and Martins, 2010).…”
Section: Lean Practices Impact On Production Swiftness and Evennessmentioning
confidence: 99%
“…Frequency of occurrence in literature for quality, etc., and hence fails in achieving the common objective, which is the end user satisfaction. Especially electronics organizations should form collaborative partnerships with suppliers and share market demand information, which would help these firms to tackle bullwhip effect, as this electronics industry involves several supply chain entities from retailer through manufacturer EB 22 No measure for reducing set up time (Lee and Ebrahimpour, 1984;Dora et al, 2014;Saravanan et al, 2018) The organization does not take care of improving setup time, though set up time is found to directly influence product lead time, customer responsiveness and amount of work in process inventory, thereby affecting smooth operation and incurring high carrying costs 3 EB 23 Lack of cohesive research and development road map (Antony et al, 2016;Devi et al, 2013) The organization lacks expertise in innovative activities like development of new products and processes and effectively improving existing products in response to customer feedback 2 EB 24 Changing governmental policies (Devi et al, 2013) The organization does not adapt itself to the changes in economic policies and market regulations of the government from time to time, which will affect competitiveness and profitability of the organization 1 Table I.…”
Section: Sno Lean Barrier Descriptionmentioning
confidence: 99%
“…Running small Lean projects in transport and logistic services (Garza-Reyes et al, 2016;Kawa et al, 2019) can induce major improvements in quality (Kuvvetli and Firuzan, 2019), reducing cost of operations and reducing lead time (SARAVANAN et al, 2018). Lean tools help to face the dilemma of improving quality, reducing cost and lead time, meeting the customer demands and providing high quality services (NAINAAR and MASSON, 2018;PONTE et al, 2018).…”
Section: Introductionmentioning
confidence: 99%